(3GdJfejI GdSjGSjI GdJfejI GdGbJUGOjI hGdGefs - (3eMeO(B, (3NGJejs ((3HjQhJ(B:s (3OGQ GdacQ GdeYGUQ(B,s, 2002)
(3jJfGhd gPG GdcJGH bVGjG MSGSI JJYdb HGdJfejI ajg GfNQW GdSjO eMeO NJGej QFjS GdLeghQjI GdGSdGejI GdGjQGfjI aj GdJjGQ GdYbdGfj GdPj jbOe faSg HOjdG Yf fehPL GdNhGQL hQhGSHg GdJj JSQHJ Gdi JQGK GdGSdGe GdacQj hgh eG jaJC jQOO HUOhQ eTQhYg GdSjGSj Cf GdMcheI GdbhjI JSJhYH MbjbI adSaIjh hJchjfjI JajO HCf GdGNJdGa aj hLgGJ GdfXQ CeQ jTcd YGedG gGeG Yf YhGed Jbe GdeLJeY GdGSdGej HCfgG JfHKb ef Ueje GdJLQHI aj OhdI JNVY dSjGbGJ JCKjQ eJfhY hJSJhYH LhGfH YedjI GdJMOjK hHfGA GdeOfj hJdGeS ChLGY GdGfSGf hgeheg , eJMGjI HUQGMI bdeG jLOgG dOi eSDhd QSej eKdg (B.s
Keywords: (3JfejI SjGSjI (B- (3JfejI GbJUGOjI (B- (3Gefs